TERMINOLOŠKE ODREDNICE ELEMENATA TEHNIKE SRPSKIH NARODNIH PLESOVA - Vladimir Mutavdžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
It is evident that terminology and names of folk dance technique elements are very different therefore very frequently a dance pattern appears to be very unclear and it is difficult to be interpreted. That is not the case with dances that have simpler dancing technique, but, primarily, with more complex ones due to inappropriate terminological solutions that are imprecise. Of course, there is a corresponding terminology in ethnocoreology but it is too wide and gives ethno-coreologists more freedom. There is also a corresponding terminology with its characteristics in physical culture and sometimes it is difficult to apply it to folk dance. Therefore, for the purpose of establishing as clear and precise terminological references as possible, a solution should be sought, which is recommended, in a compromise between terminologies of ethno-coreology and the physical culture as a science. The simplest and the most acceptable thing to do is to distinguish the most characteristic technique elements of the folk dances of Serbia, those upon which the greatest part of the performance technique rests and, in recording, separately for each of the folk-dances wherever it is needed, to explain the dancing patterns